MOTIVASI DAN MODAL SOSIAL PETANI DALAM PENGAMBILAN KEPUTUSAN PINJAMAN KREDIT PERTANIAN DI KAMPUNG YASA MULYA DISTRIK TANAH MIRING - Wakhidi Wakhidi; Marthen A.I Nahumury; Maria M. D Widiastuti (Universitas Musamus, Merauke, Papua, 2016)
The purpose research is to analyze the influence of motivation and social capital towards the agricultural credit loan decision in Kampung Yasa Mulya District Tanah Miring. This research was conducted for two months, from June to July 2016. The sample used Proportional Random Sampling method and the data analysis using binary logistic regresion. The results showed that motivation () and sosial capital () with significant level 95%, significant influence on the farmer decisions of the agricultural credit with a value is 0.027 and 0.004. The farmer who have motivation, 3,155 times higher in the decision on get the agriculture credit loans than other farmer. The farmer who have sosial capital, 4,231 times higher in the decision on get the agriculture credit loans than other farmer. According to the result, financial institution which facilitate agricultural credit loan can provide the best services by socialization of agricultural loans directly to individuals or farmers group.